Wealth: its use, level, inheritance and change: in relation to human capital - Jonathan Gershuny (University of Essex, Institute for Social and Economic Research (ISER), 2002)
This paper investigates a number of conjectures about the relative importance of the two components of social class, wealth and human capital, through the life course. It sets out grounds for the expectation that human capital will be of more importance to social position during the earlier part of adult life, while wealth should be increasingly important during the later. The empirical part of the discussion develops a predominantly indirect estimation of wealth (by multiplying up from observed income from investments and pension funds from the British Household Panel Study), also using BHPS direct measures of housing wealth. The distribution of these two measures over the life-course (estimated cross-sectionally) conforms to the expected life-course pattern. Regression models are used to show the importance of human capital growth for the accumulation of capital through the life-course.
Keywords: 330